The role of psychological factors in health and illness : the application and future direction of health psychology in Malaysia - Abdul Majid, Hariyati Shahrima (Thomson, 2005)
This aim of this chapter is to introduce health psychology as a branch of applied psychology in Malaysia. The chapter is divided into the following sections: (1) overview of health psychology; (2) literature review on psychological factors associated with health and illness-related behaviors; (3) health and illness in Malaysia; (4) major landmarks ofhealth psychology in Malaysia; and (5) coronary heart disease among Malaysians referring to a study on the relationship between psychological factors and outcomes. The rationale for addressing coronary heart disease (CHD) is multifold: (i) CHD is the leading mortality factor in Malaysian government hospitals; (ii) the onset and progression ofCHD is influenced by modifiable healthrelated behaviors; and (iii) cardiac rehabilitation programs in Malaysia need to take into account the specific psychological needs of Malaysian